Modelling the bycatch reduction of a shrimp trawl with a combined Nordmøre grid and sieve panel configuration in the north east Atlantic deep-water shrimp (Pandalus borealis) fishery - Jacques, Nadine Louise (UiT The Arctic University of Norway, 2018)
The aim of this study was to investigate whether a sieve panel could be an alternative to the Nordmøre grid or if a sieve panel could combine with the Nordmøre grid regarding bycatch reduction while simultaneously maintaining shrimp retention in the Northeast Atlantic deep-water shrimp (Pandalus borealis) fishery. These gears are the two most established bycatch reduction devices used today in shrimp fisheries internationally. Despite this, the incidental capture of non-target species, in particular the juvenile populations, continues to attract worldwide attention. This challenge was addressed by analyzing the selectivity of shrimp as well as three different bycatch species when the sieve panel replaced the Nordmøre grid. Alternatively, selectivity with a combination of the two was quantified using a special bootstrap technique. Passage was examined using four different sieve panel configurations (adjusting mesh size and sieving angle). When the sieve panel replaced the Nordmøre grid shrimp loss was higher when the small mesh size was used and unaffected with a large mesh size. Bycatch exclusion with a small mesh size was superior, with passage probability being almost consistently significantly higher through the sieve panel than the Nordmøre grid. When the selective devices were combined, small meshes again led to much more shrimp loss, while the large meshes added approximately just 3% shrimp loss. Based on the results, this thesis demonstrated that a combination of a sieve panel, configured in the correct way, followed by a Nordmøre grid provides an opportunity to significantly reduce bycatch while simultaneously retaining shrimp. The results and the potential use of the methods in practice are discussed.